HUBUNGAN REGULASI EMOSI DENGAN PERILAKU ALTRUISME ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA 3 KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Zilliya Ayuni; Hukmi Hukmi; Ria Novianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to know the regulation of the relationship of action and behavior of children aged 5-6 years in TK Negeri Pembina 3 subdistrict Marpoyan Damai City Pekanbaru. The population of this research is a child aged 5-6 years in TK Negeri Pembina 3 District Marpoyan Damai Kota Pekanbaru, amounting to 100 children. The method used is a correlation of Pearson Product Moment. The data collection techniques used are observations. Data analysis techniques using scale trials and statistical method analysis with IBM SPSS Ver. 23 program. Based on the exactionable hypothesis test Hasi There is a positive and significant relationship between the emotional regulation with the behavior of the aged 5-6 years in TK Negeri Pembina 3 subdistrict Marpoyan Damai City Pekanbaru. It can be known from the value of the correlation coefficient of rxy = 0.377 and the equivalent significance of 0.000 < 0.05. The level of interaregulation of emotion with the behavior of a Perilakualtruismeanak 5-6 know in TK Pembina 3 subdistrict Marpoyan Peace City Pekanbaru belongs to the category of a percentage value of 70.64%. Based on the results of the hypothesis test obtained there is a positive and significant relationship between the behavior of altruism children aged 5-6 years in TK Negeri Pembina 3 subdistrict Marpoyan Damai City Pekanbaru. It can be known from the value of correlation coefficient of rxy = 0.377.Key Words: Emotional Regulation, Behavior Of Altruism